EVALUASI PERENCANAAN DAN IMPLEMENTASI DAK FISIK PENUGASAN BIDANG PASAR DI PROVINSI RIAU - Andi Setyo Pambudi (Jurnal Kebijakan Pembangunan Daerah, 2022)
Market is identical with the daily activities of Indonesian people's trade. The development of market infrastructure for equitable development requires a large investment in supporting the achievement of social benefits in national development. For local governments, market infrastructure development is constrained by the limited sources of Regional Revenue and Expenditure Budget (RREB) financing. Recognizing the importance of the market for public public services, Physical Special Allocation Fund (SAF) is an attractive option for regions to cover this shortfall. This study uses a mixed method approach through questionnaire-based analysis, Focus Group Discussion (FGD), literature study of central-regional planning documents and field visits. This study aims to evaluate the degree of linkage between physical SAF planning and regional development planning. Of the 34 provinces in Indonesia, there are 31 provinces that do not include the Market Sector activity menu in the Annual Regional Development Planning (ARDP). Specifically, the results of the analysis show that Riau Province, which received the largest physical SAF budget for Market Sector Assignments, nationally has not been optimal in responding to it in its regional planning documents, especially regarding regional priorities. Based on filling out the questionnaire, all LGTO (Local Government Technical Office) managing the Physical SAF for the Market Sector stated that they agreed that the implementation of SAF activities was running smoothly and that the realization of budget distribution was on time. As many as 75 percent of LGTO stated that the amount of matching funds was not allocated enough by the regional government, the allocation was not proportional enough, SAF activities were not in accordance with regional needs and the SAF budget was insufficient.